Implementation of iPads to Increase Compliance With Delivery of New Parent Education in the Mother-Baby Unit: Retrospective Study - Haritha Pavuluri; Alicia Grant; Alexander Hartman; Lauren Fowler; Jennifer Hudson; Patrick Springhart; Ann Blair Kennedy (JMIR Publications, 2021)
BackgroundAbusive head trauma (AHT) is a serious health problem affecting more than 3000 infants annually in the United States. The American Academy of Pediatrics and the Centers for Disease Control and Prevention (CDC) recommend that health care providers counsel new parents about the dangers of AHT. Previous studies demonstrate that parental education is effective at reducing AHT events. South Carolina law requires hospitals to offer all new parents with the opportunity to watch an educational video about AHT. This mandate is addressed in different ways at the several delivery centers within a large South Carolina health care system with a range of viewing methods utilized, from DVD players to mobile workstations to personal devices. Frequent technical barriers and workflow inefficiencies resulted in low rates of compliance with this mandate at several campuses. To improve compliance of parent viewing of this educational video, the health care system standardized video viewing protocol across all campuses by implementing the use of iPads for parental education. Existing literature suggests that patient education can be improved in the hospital setting by utilizing tablet computers, but our literature search identified a gap in research around the education of parents and caregivers during hospitalization for childbirth. We used the implementation of an iPad-based parental education delivery protocol to evaluate whether tablet computers can improve compliance with delivering new parent education in the hospital setting. ObjectiveThe objective of this study was to evaluate whether the standardized use of iPads to deliver education in the mother-baby unit resulted in improved rates of parents' acceptance of the opportunity to view an educational video about AHT. MethodsWe interviewed physicians and nurses to determine what previous protocols were in place to educate new parents before a standardized iPad-based protocol was implemented across 6 campuses of a large South Carolina health care system. A retrospective study was conducted by review of 5231 records from across the 6 campuses to determine the pre- and postintervention compliance rates of viewing the AHT educational video by parents in the mother-baby unit. ResultsCompliance increased overall (P<.001) across sites from an average of 41.93% (SD 46.24) to 99.73% (SD 0.26) (φ=0.510). As much as 4 of 6 locations saw a significant increase in compliance rates after introducing the iPad intervention (P<.001). The remaining 2 locations that showed no significant difference (P>.05) had very high rates of preintervention compliance. ConclusionsFollowing the implementation of a standardized iPad-based protocol to deliver new parent education, there was a significant improvement in the percentage of new parents who viewed an educational video about AHT in the mother-baby unit. Based on these results, other health care providers should consider iPads to be a feasible and effective method for delivering hospital-based education to families in the mother-baby unit.